The Associations Between Parental Burnout and Mental Health Symptoms Among Chinese Parents With Young Children During the COVID-19 Pandemic - Chen, Minglong; Bai, Yashuang; Fu, Mingqi; Huang, Ning; Ahmed, Farooq; Shahid, Muhammad; Wang, Xiaohua; Liu, Chengbin; Feng, Xing Lin; Guo, Jing (Frontiers in Psychiatry, 2022)
The Coronavirus Disease 2019 (COVID-19) pandemic has caused numerous unexpected changes for families and societies, which have likely contributed to higher amounts of stress for most parents. This study aimed to examine the relationship between burnout and mental health among parents during the COVID-19. Pandemic exposure and household factors (e.g. family structure, family function) were examined as moderators. An online cross-sectional survey recruiting 1209 adults was conducted from April 21st to April 28th, 2020 during the COVID-19 lockdown in China. The multivariable linear regression analysis was employed to test the association between burnout, household factors, and mental health among parents. Findings suggested that for parents with a young child, poorer mental health was related to a higher level of burnout (β=0.220, P<0.001) and greater exposure to the pandemic. Mothers of a single and/or young child had considerably poorer mental health. Moreover, the relationship between mental health and burnout among parents was significantly moderated by epidemic exposure (β=2.561, P<0.001), family structure (number of children: β=-1.257, P<0.001; first child age: β=-1.116, P<0.001) and family function (β=-0.574, P<0.05). This study indicated that burnout symptoms were significantly associated with worse mental health among parents in China. Besides, exposure to the pandemic, family structure, and family function was found to moderate the association between burnout and mental health among parents. Therefore, the present study stressed enhanced access to mental health resources and emotional supports for parents during a public crisis to reduce the deleterious effects of burnout.